Funkcjonowanie i kierunki rozwoju przedsiębiorstw dystrybucyjnych jako skutek procesów zmian w polskim sektorze energetycznym - Nogalski, Bogdan; Mazur-Jelonek, Aneta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This article presents results of the identification process and assessment of the actual state in the stribution companies, after changes that occurred during the last ten years. Against this background, is a possibility of development of these companies and this strategic sector. The changes that had taken place in this sector influenced the companies in a way that they took charge of their activity and development. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 131-141